BEATA ZIÓŁKOWSKA, JOWITA WYCISK, SELF-DESTRUCTION OF CHILDREN AND YOUTH - JAWORSKA, JOANNA (Society Register, 2019)
Anyone who works with the youth knows that the period of adolescence is a specific life-phase for young students. “Socio-cultural changes, changing family patterns, too many incentives and the social pressure in many areas of human’s life” (p. 252) can cause problems, and teenagers often don’t deal appropriately with their feelings, emotions, and expressions. Also during this time, we have come to expect different and often rebellious, as well as undesirable behaviour from the young boys and girls. Every teacher, educator or someone who takes care of such young people, is inclined to support them effectively and when the functional disorders start to appear, they want to react positively towards them and work together to solve their problems. For those people, I would highly recommend the book “Self-destruction children and youth” written by Beata Ziółkowska and Jowita Wycisk.